2019
DOI: 10.1038/s41598-019-55980-4
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol attenuates inflammation by targeting HMGB1 through upregulating miR-339-5p

Abstract: Sepsis is a life-threatening disease caused by infection. Inflammation is a key pathogenic process in sepsis. Paeonol, an active ingredient in moutan cortex (a Chinese herb), has many pharmacological activities, such as anti-inflammatory and antitumour actions. Previous studies have indicated that paeonol inhibits the expression of HMGB1 and the transcriptional activity of NF-κB. However, its underlying mechanism is still unknown. In this study, microarray assay and reverse transcription-quantitative polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…The extracellular release of HMGB1 is induced when cells are stimulated, and HMGB1 is considered an important new target for treating various inflammatory diseases, including brain injury and cancer (Sun and Chao, 2005;Das et al, 2021). Some other studies revealed that Paeonol reduces sepsis by promoting the miR-339-5p expression to repress the HMGB1 and IKK-β-mediated inflammation (Mei et al, 2019). During the process of IDD, HMGB1 is significantly upregulated in the intervertebral disc (IVD) and promotes the expression of inflammatory cytokines such as prostaglandin E2 (PGE2), TNF-α, IL-6, and IL-8 and matrix metalloproteinases (MMPs) (Rajan et al, 2013;Fang and Jiang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular release of HMGB1 is induced when cells are stimulated, and HMGB1 is considered an important new target for treating various inflammatory diseases, including brain injury and cancer (Sun and Chao, 2005;Das et al, 2021). Some other studies revealed that Paeonol reduces sepsis by promoting the miR-339-5p expression to repress the HMGB1 and IKK-β-mediated inflammation (Mei et al, 2019). During the process of IDD, HMGB1 is significantly upregulated in the intervertebral disc (IVD) and promotes the expression of inflammatory cytokines such as prostaglandin E2 (PGE2), TNF-α, IL-6, and IL-8 and matrix metalloproteinases (MMPs) (Rajan et al, 2013;Fang and Jiang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has confirmed that herbs in traditional Chinese medicine (TCM) are effective in treating neurodegenerative diseases of the CNS, including Alzheimer's disease (AD) [21,22], amyotrophic lateral sclerosis (ALS) [23], and MS. Previous studies have shown that numerous prescriptions and herbal extracts of TCM have protective effects against diseases by modulating various miRs [24][25][26][27]. Thus, it is reasonable to explore new therapeutic strategies based on TCM to treat MS. Bu Shen Yi Sui capsule (BSYS) was modified from the Liu Wei Di Huang pill, a well-known traditional Chinese formula, which has been used for 10 years in MS clinical treatment at Tiantan Hospital (Beijing, China).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-339-5p is upregulated to alleviate neuroinflammation by inhibiting HMGB1 [ 106 ]. HMGB1 encodes high mobility group box 1 to produce proinflammatory cytokines by binding to receptors for advanced glycation end products (RAGE) [ 107 ] and inhibiting IKK-β and IKK-γ, which are key elements of NF-κB signaling [ 108 ].…”
Section: Resultsmentioning
confidence: 99%